Role of identity in shaping the well-being of Kazakh youth - М. Ақмади; Д. Бурханова; Г. Кенжакимова; Я. Пак (Хабаршы. Психология және социология сериясы)
The relationship between identity and well-being is one of the central themes of modern sociological research, especially in youth studies. The present study aims to analyze the influence of different identity styles (informational, normative, and diffuse-avoidant) on well-being indicators among young people aged 18 to 35. An integrated methodology was used to achieve the goal, including the ISI-5 identity style survey and the Gallup Healthways Well-Being Index. The ISI-5 questionnaire evaluates three styles of processing identities: informational, related to active search and analysis of information; normative, based on following social norms and expectations; and diffuse-avoidant. The avoidance of complex decisions and thinking about the future. The Gallup Healthways Well-Being Index measures well-being across six key dimensions: subjective life assessment, emotional and physical health, healthy behavior, satisfaction with the work environment, and access to essential resources. The survey covered all regions of Kazakhstan, including republican cities, regional centers, and rural settlements. Data collection was conducted in Kazakh and Russian, considering respondents' preferences. The study results showed that the informational identity style positively affects emotional resilience and life satisfaction, while the normative style promotes stability and a sense of security. In contrast, the diffuse-avoidant style temporarily reduces stress but limits long-term life prospects. The study's results significantly contribute to the study of the relationship between identity and well-being, complementing the existing literature with new empirical data. The study's practical significance lies in its use for developing social policies and programs to strengthen the well-being of young people under socio-economic and cultural transformations in Kazakhstan.